Model Matematika Metode Penjejak Parameter Sebagai Pemerkira Parameter Fisikawi Bahan Makanan - Budi Rahardjo (agriTECH, 1993)
Parameter tracking method was used to estimate mathematically the physical parameters of food. Five mathematicalmodels of the food properties were studied: linear model with one parameter, linear model with two parameters, non linear model with two parameters, exponential model with two parameters and non linear model with three parameters. The parameters of the first four mathematical models can be estimated using the parameter tracking method. Analytical solution of the fifth model that indicates whether the parameters will converge to their real values can not be found.